Improving Mathematics Learning Outcomes for Whole Numbers Materials Through an Active Learning Model Type Index Card Match (Icm) for Class 1 Students at State Elementary School Cibentang 01 Semester I 2019/2020 Academic Year - Setyawati, Nunung (Universitas Sebelas Maret, 2020)
This research is a collaborative classroom action research with the research subject of teachers and students of class 1 SD Negeri Cibentang 01 totaling 22 students. The object of this research is the result of learning mathematics through an Active Learning model of Index Card Match type on whole numbers. This research was conducted for two cycles. The results showed an increase in mathematics learning outcomes after using the Index Card Match Active Learning model according to the syntax in the first cycle. The increase again occurred after modifications were made with discussion, the use of rewards, and the addition of quiz rules in the second cycle. The increase occurred in the cognitive value from 70.68 in the pre-cycle to 84.95 in the second cycle. The affective aspect increased from 2.47 (good) in the first cycle to 3.04 (good) in the second cycle. The use of the Active Learning model with the Index Card Match type until the second cycle obtained data > 75% of all students scored 70 so that the mathematics learning process using the Index Card Match type Active Learning model is considered to be able to improve student learning outcomes.